2018
DOI: 10.1371/journal.pone.0207694
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic self-stimulation in the nucleus accumbens: D1 reward versus D2 ambivalence

Abstract: The nucleus accumbens (NAc) contains multiple subpopulations of medium spiny neurons (MSNs). One subpopulation expresses D1-type dopamine receptors, another expresses D2-type receptors, and a third expresses both. The relative roles in NAc of D1 neurons versus D2 neurons in appetitive motivation were assessed here. Specifically, we asked whether D1-Cre mice would instrumentally seek optogenetic self-stimulation specifically targeted at D1 MSNs in NAc, and similarly if D2-Cre mice would self-stimulate D2 neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 62 publications
9
76
3
Order By: Relevance
“…Furthermore, our data do not support the hypothesis that Drd1 and Drd2 MSNs act in opposing manner [73] but rather, suggests that a coincident and concerted MSNs activity is required for reward-related behaviors [74][75][76]. Indeed, regardless of the antagonist used in our experiments (SCH39166, Drd1selective; raclopride, Drd2-selective; flupenthixol, Drd1-Drd2-selective), we observed reliable reduction of incubation of methamphetamine craving.…”
Section: Role Of Nac Drd1-and Drd2-msns During Incubation Of Methamphcontrasting
confidence: 91%
“…Furthermore, our data do not support the hypothesis that Drd1 and Drd2 MSNs act in opposing manner [73] but rather, suggests that a coincident and concerted MSNs activity is required for reward-related behaviors [74][75][76]. Indeed, regardless of the antagonist used in our experiments (SCH39166, Drd1selective; raclopride, Drd2-selective; flupenthixol, Drd1-Drd2-selective), we observed reliable reduction of incubation of methamphetamine craving.…”
Section: Role Of Nac Drd1-and Drd2-msns During Incubation Of Methamphcontrasting
confidence: 91%
“…We note that other studies have reported distant increases in Fos in VP, LH, and VTA to be induced by ChR2 stimulation of NAc MSN populations (Cole et al, 2018;Soares-Cunha et al, 2018).…”
Section: Anatomical Placements Of Optic Fibers and Microinjections Insupporting
confidence: 47%
“…Similarly, changes induced by DNQX microinjections were computed by comparison to a vehicle-microinjection baseline. For that, Fos was measured in equivalent sites in rats that received vehicle microinjections 90 min before perfusion (Castro and Berridge, 2017;Warlow et al, 2017;Cole et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The failure of NAcc inhibition to suppress nose poking may seem odd. Mice will readily perform actions that channelrhodopsin-excite NAcc D1 and D2 cell types (Cole et al, 2018), and rats will perform actions exciting glutamatergic inputs to the NAcc via channelrhodopsin (Stuber et al, 2011;Britt et al, 2012). However, these studies demonstrate that NAcc activity is sufficient, but not necessary, to support reward-seeking.…”
Section: Discussionmentioning
confidence: 99%